MILITARY INTERVENTION IN CONFLICT SITUATIONS IN AFRICA: THOUGHTS ON SOUTH AFRICA'S ROLE (The Strategic Review for Southern Africa, 2020)
Almost 20 years after it took place, the Rwanda genocide of 1994, in which over 800 000 persons were slaughtered in 100 days while the world stood and watched, continues to haunt Africa. When the African Union (AU) was born, provision was made in its Constitutive Act, signed in 2000, to authorise military interventions, to prevent a Rwanda-type catastrophe ever happening again. But a decade later Africa remains unready to intervene where threats of mass killings arise, as the cases of Libya and Mali have recently shown. In 2011, after the United Nations Security Council (UNSC) had authorised the use of "all necessary force", the North Atlantic Treaty Organisation (NATO) intervened militarily in Libya when there appeared to be a threat that the regime there was about to slaughter civilians in Benghazi. In 2012 France sent troops to Mali to prevent a rebel force that had committed massacres in the north advancing south to the capital, Bamako. The side-lining of Africa in the Libya and Mali crises, and the decision by the NATO countries to move from dealing with the perceived threat of civilian massacres in Libya to regime change, forced African leaders to give new thought to the idea of "African solutions for African problems". Africa should, it was said, have the capacity to intervene in conflict situations.